Effects Of The COVID -19 Pandemıc On The Elderly: A Grounded Theory Study From Turkey - Koşar, Ahmet; Kasapoglu, Aytul (Advances in Social Sciences Research Journal, 2021)
More than 95 percent of those who lost their lives as a result of the spread of the Covid-19 virus to the world since the beginning of 2020 are over the age of 60 (WHO, 2020). The main purpose of this article is to reveal the vital difficulties of the 65-75 age group in Turkey, who were quarantined due to the Covid-19 pandemic, as a result of deprivation of their former normal lives and how they overcame them. The theoretical starting point of this study is the relational sociologist H. White and his “uncertainty” classification. In the study, Grounded Theory Methodology was chosen as one of the qualitative research approaches and open, axial and selective codings were made as a requirement of this. In this context, interviews were made with 12 individuals from the 65-75 age group and the data were presented in figures. As a result of open, axial and selective coding, the core concept of the study was determined as "solidarity". In accordance with the grounded theory, at the end of the study, the "solidarity process" was narrated using the "river" metaphor.